2017
DOI: 10.3892/etm.2017.5496
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of berberine against learning and memory deficits in diffuse axonal injury

Abstract: Abstract. The aim of the present study was to assess the neuroprotective effect of berberine against learning and memory deficits in diffuse axonal injury (DAI). DAI rats were orally gavaged with berberine at a dose of 200 mg/kg of body weight for 4 weeks. Behavioral tests were used to analyze the neuroprotective effect of berberine against DAI-induced learning and memory deficits. In the present study, treatment with berberine significantly protected against DAI-induced inhibition of learning and memory in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…One study intentionally compared outcomes after moderate and severe TBI (Davis et al., 2008), otherwise investigations focused on evaluating a NUT following a specific severity of TBI. Two studies evaluated a NUT following repetitive TBI (Wang et al., 2018; Zhang et al., 2018). In both studies animals suffered three TBIs by either FPI or Marmarou weight drop to produce repetitive mild and severe TBIs, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One study intentionally compared outcomes after moderate and severe TBI (Davis et al., 2008), otherwise investigations focused on evaluating a NUT following a specific severity of TBI. Two studies evaluated a NUT following repetitive TBI (Wang et al., 2018; Zhang et al., 2018). In both studies animals suffered three TBIs by either FPI or Marmarou weight drop to produce repetitive mild and severe TBIs, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…KD (Deng-Bryant et al, 2011;Greco et al, 2016;Hu, Wang, Jin, et al, 2009;Hu, Wang, Qiao, et al, 2009;Prins et al, 2005;Prins & Hovda, 2009;Schwartzkroin et al, 2010;Zhang et al, 2018);6. multi-supplements (Thau-Zuchman et al, 2019;Wu et al, 2014); 7. ω-3 polyunsaturated fatty acids (PUFAs) (Bailes & Mills, 2010;Mills et al, 2011;Schober et al, 2016;Shin & Dixon, 2011;Su et al, 2016;Wu et al, 2011;Zhu et al, 2017); or 8. natural compounds used in traditional eastern medicine (Kumar et al, 2014;Özevren et al, 2018;Sharma et al, 2010;Wang et al, 2018;Xie et al, 2018;Xing et al, 2016;Zhao et al, 2014). for each study is available in Table S1.…”
Section: Nutritional Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous studies that showed that berberine has central nervous system activity [ 50 ]. Berberine has also been shown to have neuroprotective effects on learning and memory impairment in rats with severe diffuse axonal injury by inhibiting inflammation, angiogenesis, and apoptosis [ 51 ]. The results of one study showed that berberine affected ErbB signaling pathway in insomniac rats, and it could affect the production of several sleep-promoting substances [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also exerts other activities such as anti-inflammatory, anti-diabetic, lipid per-oxidation, neuro-protective activity and most importantly anticonvulsant activity. 14,15 Subsequently the next strategy was 'adaptation of nanotechnology which positively impacts the efficacy improvement since nanotechnology is a powerful platform and most promising strategy to CNS drug delivery, by which the drugs are efficiently delivered to the brain, by crossing the blood brain barrier. 16 By utilising both the strategies, the phenytoin and berberine nanoparticles were formulated (Individually) through solvent evaporation and sonication methods and they were loaded in the 1" sized hard gelatine capsules designed as a single unit dosage and later on the nanoparticles were optimized by in vitro release and entrapment efficiency.…”
Section: Introductionmentioning
confidence: 99%